2021
DOI: 10.46419/vs.53.3.8
|View full text |Cite
|
Sign up to set email alerts
|

βeta-lactam and Tetracycline Antibiotic Residues in Cow Milk in the Constantine region, Algeria

Abstract: The aim of the present study was to investigate the βeta-lactam and tetracycline antibiotic residues in cow milk samples. A total of 122 samples of cow milk were collected from raw milk collectors (109 samples) and from a reconstituted pasteurized milk sales clerk (13 samples) in the Constantine region, Algeria and examined using the ΒetaStar Combo screening kit (Neogen, USA). Results indicates that 13 samples (10.66%) were positive for antibiotics residues: 12 (9.84%) for βeta-lactams (ten (8.20%) raw and two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Tetracycline Combo test was used and it was found that 4.2 % of the samples were tested positive for β-lactam and tetracycline residues [24]. In Benin, milk was tested using the Twin Sensor kit 020 and the result showed 83.9 % positivity for β-lactam and tetracycline residues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tetracycline Combo test was used and it was found that 4.2 % of the samples were tested positive for β-lactam and tetracycline residues [24]. In Benin, milk was tested using the Twin Sensor kit 020 and the result showed 83.9 % positivity for β-lactam and tetracycline residues.…”
Section: Discussionmentioning
confidence: 99%
“…In Benin, milk was tested using the Twin Sensor kit 020 and the result showed 83.9 % positivity for β-lactam and tetracycline residues. They believe the most common cause of the presence of antibiotic residues in milk is non-compliance with the period for antibiotic excretion from the animal body, followed by overuse of banned antibiotics [24]. Other causes may include the therapeutic or prophylactic misuse of antibiotics and violation of the withdrawal period, illegal use of antibiotics or use of antibiotics as growth promoters [11].…”
Section: Discussionmentioning
confidence: 99%
“…So far, many researches on presence of antibiotics in milk have been conducted. [14][15][16][17][18][19][20][21][22] It has been reported that the use of kits can sometimes lead to false results. However, different kits are used to detect the presence of antibiotics in factories.…”
mentioning
confidence: 99%